The Implementation of The Punishment of Whipping In Aceh From A Legal and Human Rights Perspective - Ahmad Baiza (International Journal of Social Service and Research, 2023)
Ranch "Rahmat Aulia" incorporated in section PT Charoen Pokphand Jaya Farm, ranch located in the village of the District Kutatrieng Labuhanhaji South Aceh Barat have been using management are good in financing that covers the cost of production, the cost of marketing, and salaries of employees. Selection of research on the farm "Rahmat Aulia" in because of the high level of competition of sales in the business of chicken broilers (Gallus dometicus) with this research can be expected as a reference for the novice and the other farmers in the face of competition. The type of research used is a qualitative type (interview). Where data collection using interviews with relevant parties on the farm "Rahmat Aulia" as a resource, as well as samples that used the financial statements of the farm "Rahmat Aulia" which has been recorded in PT Charoen Pokphand Jaya Farm in the year 2021 (3 months). The results of the study stated that 80% of sales result were strongly influenced by production costs, and marketing costs, and employee salaries. While the remaining 20% of sales are influenced by other factors that are not explained in this study. From the analysis, the results show that production costs, marketing, and employee salaries play a very important role in the sustainability of the “Rahmat Aulia” farm in Kutatrieng Village, Labuhanhaji Barat district, South Aceh regency.